Limitations of Viewing in Khitbah: A Comparative Study of the Thoughts of Ibn Hazm and Wahbah Az-Zuhaili and Their Relevance to Indonesian Muslim Culture - Amrin Borotan; Sahrin (Islamic Circle, 2025)
Khitbah is a pre-marital phase recognised in Islamic jurisprudence as a means of Ta’ruf before the marriage contract is concluded. One important issue in khitbah is the limits of what is permissible in terms of seeing one's prospective spouse, which in practice is often misunderstood and exceeds the limits of Sharia ethics, especially in the context of modern Muslim society. This study aims to analyse the concept of limits on seeing in khitbah according to fiqh, conduct a comparative study of the thoughts of Ibn Hazm and Wahbah Az Zuhaili, and examine its relevance to Indonesian Muslim culture. This study is a normative Islamic legal study with a comparative approach, using a literature study of classical and contemporary fiqh books as the main source. The results show that Ibn Hazm permits viewing all parts of the prospective spouse's body based on the textual approach of the Zahiriyah school of thought, while Wahbah Az Zuhaili limits it to only the face and both palms out of caution and to prevent mafsadat. In the context of Indonesian Muslim culture, where the meaning of khitbah has shifted to resemble dating, the views of the majority of scholars as explained by Wahbah Az Zuhaili are considered more relevant for maintaining pre-marital social ethics. This study emphasises that restrictions on viewing during khitbah have practical implications for the moral and social development of Muslim communities